2016
DOI: 10.1073/pnas.1616574113
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model for acute Epstein–Barr virus infection

Abstract: Epstein-Barr Virus (EBV) infects human B cells and drives them into continuous proliferation. Two key viral factors in this process are the latent membrane proteins LMP1 and LMP2A, which mimic constitutively activated CD40 receptor and B-cell receptor signaling, respectively. EBVinfected B cells elicit a powerful T-cell response that clears the infected B cells and leads to life-long immunity. Insufficient immune surveillance of EBV-infected B cells causes life-threatening lymphoproliferative disorders, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 38 publications
6
49
0
Order By: Relevance
“…GC B-cell LMP1 and LMP2A expression was necessary for induction of fatal lymphoproliferative disease in our model. This result is in agreement with prior LMP2A models, where transgenic LMP2A expression from an early stage in B-cell development alone or together with LMP1 (12,31,32), or alone in GC B cells (19). Interestingly, we did not observe disease in LMP1 AID T/NK-cell-deficient mice over a 14-d interval.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GC B-cell LMP1 and LMP2A expression was necessary for induction of fatal lymphoproliferative disease in our model. This result is in agreement with prior LMP2A models, where transgenic LMP2A expression from an early stage in B-cell development alone or together with LMP1 (12,31,32), or alone in GC B cells (19). Interestingly, we did not observe disease in LMP1 AID T/NK-cell-deficient mice over a 14-d interval.…”
Section: Discussionsupporting
confidence: 93%
“…Our results, together with the results of another recent mouse model of GC LMP1/2A coexpression (32), build on the observations that LMP2A augments LMP1 signaling (36,37) and that LMP1/2A synergistically accelerate carcinogenesis (38). CD19 promoter-driven LMP1/2A coexpression from early in B-cell development, but not CD19-driven expression of LMP1 or LMP2A alone, causes fatal neonatal lymphoproliferative disease (32).…”
Section: Discussionsupporting
confidence: 83%
“…EBV latency II is observed in Hodgkin lymphoma (HL) and also in NPC. GC B-cell LMP1 and LMP2A coexpression causes rapidly fatal lymphoproliferative disease in T-cell deficient mice (68), further highlighting the key role of immune surveillance in countering LMP1 oncogenicity. NK cells also have key host defense roles necessary for host defense against EBV, and combined T/NK-cell depletion results in massive LMP1/ LMP2A-driven GC B-cell outgrowth, plasmablast differentiation, and death within 12 days (69).…”
Section: Mouse Models Of Lmp1 Lymphomagenesismentioning
confidence: 97%
“…3 In mouse models transgenic for Epstein-Barr virus antigens LMP1 and LMP2, lymphoproliferative disease is also controlled by T cells. 34,35,38 These antigens are unique because they have profound effects on the B-cell phenotype and mimic activation signals, which likely explains elimination of "activated" B cells by T cells, not necessarily LMP specific. We do not have any indication that TAg affects B-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Some of these studies demonstrated control of lymphoma development by natural killer cells, T cells, or T-cell mediators. [33][34][35][36][37][38][39] These models have given important insights into disease development but have 3 drawbacks: (1) they do not recapitulate the sporadic nature of nonviral B-cell lymphomas, (2) no antigen is known for which the mice are not yet tolerant at birth, and/or (3) no T-cell epitope is known to study specific T-cell responses.…”
Section: Introductionmentioning
confidence: 99%